PENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) SISWA KELAS IV MELALUI STRATEGI PEMBELAJARAN AKTIF BERBASIS PROYEK DI SD NEGERI 04 PARIJATAH WETAN - Faizah, Kurniatul; Kusuma, Novita (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2022)
The purpose of this research 1 ) to know how to improve learning outcomes using active learning strategy based ( project project based learning ) on subjects of science social ips ( ) class students iv second semester of public school in 04 parijatah wetan, srono school year 2014 / 2015; 2 ) to know whether or not the influence of project based learning ( project based learning ) against student learning outcomes on subjects of science social ips ( ) class students iv second semester of public school in 04 parijatah wetan, srono 2014 / 2015. school yearThis research study is a class action by using a model kemmis & amp; taggart with research, including planning stages the implementation of the act of, observation and reflection that was implemented in 2. cycleThe subject of this research fourth grade students country 04 parijatah wetan 19. interviewed studentsData collection techniques used, observation the assessment tests, and the assessment of the project. Data collection techniques use descriptive, quantitative which includes: 1 ) quantitative data student learning the test results that span the assessment of the students are classified as due diligence when achieve good <65 and unfinished when achieve good & lt; 65 and 2 ) data influence between the results of learning the project for the students with learning tests using formulas. correlational statisticsThe result showed: ( 1 ) the application of active learning strategy based on the project can improve learning outcomes eyes social studies class students iv second semester of public school in 04 parijatah wetan, srono, banyuwangi 2014 / 2015, school year this was evident on the initial conditions before carried out the act of the value of rata-rata 55 ketuntasan with the percentage of students learn as much as 32 %, in the cycle i value rata-rata 68 ketuntasan with the percentage of students learn as much as 68 %. And the cycle rata-rata class ii value increased to 82 with the percentage of ketuntasan klasikal 84 %. Thus in klasikal , the learning has reached ketuntasan learning .( 2 ) learning project had an influence on learning outcomes subjects fourth grade social studies to their students in the second semester of in public primary schools 04 parijatah wetan in 2014 / 2015 .This is proven , i cycle on the size of which is â€œrxyâ€ ( 0,783 cycle ii and in the size of the â€œrxyâ€ ( 0,769 ) has had a positive relationship with the economic situation of hig.